Subsidence, Mixing and Denitrification of Arctic Polar Vortex Air Measured During POLARIS - Rex, M.; Salawitch, R.; Toon, G.; Sen, B.; Margitan, J.; Osterman, G.; Blavier, J. F.; Gao, R.; Donnelly, S.; Keim, E.; Neuman, J.; Fahey, D.; et al. (2004)
A new technique is presented to determine the degree of denitrification that occured during the 1996/97 Arctic winter, based on balloon and aircraft borne measurements of NOy, N2O and CH4. In this study high-altitude balloon measurements are used to define the properties of air masses that later descend in the polar vortex to altitudes sampled by the ER-2 aircraft and mix isentropically with mid-latitude air.